Research in personnel and human resources management. Vol. 21 - Ferris, Gina; Martocchio, Joseph J. (Research in personnel and human resources management,, 2002)
This series publishes monograph-length conceptual papers designed to promote theory and research on important substantive and methodological topics in the field of human resources management. Volume 21 contains eight papers on critical issues in the field of human resources management, thus continuing the tradition of the series to develop a more informed understanding of the field.